Characterisation of volatile organic sulphur compounds release during coal pyrolysis in inert, hydrogen and CO2 atmosphere. (15th November 2016) - Gu, Ying; Yperman, Jan; Reggers, Guy; Carleer, Robert; Vandewijngaarden, Jens
Highlights: Different pyrolysis atmospheres result in changes in sulphur compounds evolution. For the first time organic sulphur evolution in CO2 was quantitatively determined. CO2 as reaction atmosphere results in changes of sulphur compound evolutions. Abstract: The effects of CO2 atmosphere on the distribution of volatile organic sulphur compounds during coal pyrolysis and the effect of kaolin addition were studied. Sulphur compounds release was determined by atmospheric pressure-temperature programmed reduction "on-line" coupled with MS (AP-TPR/MS) and "off-line" coupled with GC/MS after thermal desorption (AP-TPR-TD-GC/MS). The results show that thiophene and methyl and ethyl substituted analogues were released between 400 and 500 °C, while relatively more complex organic sulphur compounds such as benzothiophene and methyl benzothiophene evolved at higher temperature. In CO2, thiophenes evolved at lower temperature due to its more reactive and oxidative character. With kaolin addition, an increase in most registered volatile organic sulphur compound amounts was noticed both in inert and CO2 gas, due to the catalytic effect of kaolin.